The effect of Project Supported Education in elementary number theory course on student achievement - (:unkn) unknown (International Institute of Informatics and Systemics, IIIS, 2009)
The aim of the study is to examine the effect of Project Supported Education (PSE) on preservice teachers' achievement and thinking style. 'Post - test control group Model' is used to examine achievement results. Pre-post test control group model is used to examine thinking styles differences based on a "Thinking Style Inventory". The subjects of the study are 46 students enrolled in an Elementary Number Theory course in the Primary Mathematics Education Department in a large university in Istanbul, Turkey. Results indicate that 1) project supported education has no significant effect on student achievement and thinking styles, 2) students in the experimental group scored higher than the control group for their post-tests regarding both Anarchic and Oligarchic Thinking Styles. The reasons for these are discussed further and suggestions are provided.
Keywords: Elementary number theory; Project Supported Education; Thinking styles